Proceedings of MOL2NET 2018, International Conference on Multidisciplinary Sciences, 4th Edition 2019
DOI: 10.3390/mol2net-04-06111
|View full text |Cite
|
Sign up to set email alerts
|

<strong>Project Portfolio Optimization under Temporal Constraints with uncertainty</strong>

Abstract: The definition of more realistic scenarios of instances for the Project Portfolio Optimization (PPO) of new product developments usually should involve precedence relations that generate effects related to time-interdependence among different projects.The study of time -interdependences, or time effects, on the selection of projects captures our attention because they affect the problem objective functions. Three different moments have been identified as usually present in any project: 1) the estimated complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Such approaches have allowed the development of computable preference models, based on a predefined set of parameters that reflect the interests of a DM. The most practical way that can be used to set the parameter values for that preference model is through Preference Disaggregation Methods (Rangel-Valdez et al, 2015;Cruz-Reyes et al, 2017), which are methods that based on a battery of examples provided by the DM elicits the entire set of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Such approaches have allowed the development of computable preference models, based on a predefined set of parameters that reflect the interests of a DM. The most practical way that can be used to set the parameter values for that preference model is through Preference Disaggregation Methods (Rangel-Valdez et al, 2015;Cruz-Reyes et al, 2017), which are methods that based on a battery of examples provided by the DM elicits the entire set of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In these approaches, the provision of preference information is far simpler for a DM because it can be done based on decisions taken in the past or formulated recently by means of manageable examples. So far, PDMs have been implemented using evolutionary metaheuristics (Rangel-Valdez et al, 2015;Cruz-Reyes et al, 2017), and they have shown their effectiveness on the parameter elicitation for outranking approaches used in the solution of the Portfolio Selection Problem (PSP) with the methods ELECTRE as preference models (cf. Roy, 1991).…”
Section: Introductionmentioning
confidence: 99%